Progresso Na Seleção De Progênies De Tomate Resistentes À Murcha Bacteriana Através Da Avaliação Epidemiológica Da Doença - Noda, Hiroshi; Machado, Francisco Manoares (Acta Amazonica, 1993)
Data from experiments carried out during the decade 83/92 by the Tomato Breeding Program of the INPA were utilized to evaluate the efficience of the epidemiologic parameter Infection Rate to select resistant progenies to Pseudomonas solanacearum. Evidence were obtained that selected progenies from one to the sequence generation showed increased levels of resistance to the pathogen and yield capacity under infested soils cultivation, using standards of susceptible (Santa Cruz group) or resistente (Caraiba) varieties. The Infection Rate is able to detect high number of significant contrasts when compared to another parameter which do no consider the resistance as a resultant of a process which the expression change with the time.
Selection Progress of Resistant Tomato Progenies to Bactarial Wilt Disease by Epidemiological Evaluation
Keywords: Tomato; Pseudomonas Solanacearum; Bacterial Wilt; Tomato Breeding; Epidemiological Evaluation Of Plant Disease; Tomate; Pseudomonas solanacearum; Murcha bacteriana; Melhoramento Genético Do Tomateiro; Avaliação Epidemiologica De Doença Em Plantas